Comprendre le travail de mise en œuvre de la réforme des études en Masso-Kinésithérapie (2015) : le cas d’un institut de formation - Éric Maleyrot; Thérèse Perez-Roux; Charlotte Pourcelot; Pierre Hébrard (Activités)
This paper aims to understand, at the scale of a physiotherapy training institute, the management team’s work and that of its trainers and training tutors faced with the implementation of the 2015 studies reform. The institutional context is presented through a comparative analysis of the national physiotherapy training texts. It shows the shift from a content-centered approach to a skills-based approach related to a dual process of universitarizing and professionalizing of studies. The theoretical background develops the notions of one’s professionalization and universitarization. The research approach is based on the actor-network theory and on a qualitative data analysis (observations, focus groups, interviews) collected during the first two years of the implemented reform. The results highlight three key aspects of the process which have guided the stakeholders involved. At a macro level, the implementation of this reform shows an asynchrony affecting first the managers then the trainers close to them in the institute and finally the training tutors in the workplace. At a meso level, the tensions among the trainers reveal an ambivalent universitarization-professionalization movement. This goes from the satisfaction of theorizing their physiotherapeutic knowledge through research to the fear of a reduction in the transmission of professional gestures. Finally, at a micro level, the focus on trainers highlights their secondary professionalization, after that of physiotherapist, made necessary by the new approaches taken by the reform.